Predicción del proceso de difusión tecnológica en mercados de redes. Una aplicación empírica al caso de Internet - Arroyo Barrigüete, José Luis; Orero Giménez, Alejandro; López Sánchez, José Ignacio (Cuadernos de Estudios Empresariales, 2007)
The main objective of this paper is to propose a new model of technological diffusion in network markets, based on the value creation law proposed by Briscoe et al. (2006). After a theoretical justification, we validate the model empirically comparing, for Internet diffusion process, the predictions obtained with our model and with the most accepted ones, comparison developed evaluating the postdictive capacity of all models. The results show that the Bass model presents overfitting problems in the case of Internet diffusion. Nevertheless, the most important contribution of this paper is to demonstrate that, even in the long term (five years and a half), the predictions of our model are better than the predictions obtained with the other models analyzed. This result has a direct application for companies that operate in network markets, because the model could help them to predict the penetration of a new technology in a more accurate way than they have been doing.